Predicting clinically significant events in children with ureteropelvic junction obstruction - Wolmer, Clara; Delmas, Jean; Pecorelli, Silvia; Dobremez, Eric; Ferdynus, Cyril; Harper, Luke (Frontiers in Pediatrics, 2024)
Introduction: Ureteropelvic junction obstruction (UPJO) syndrome is one of the most common causes of neonatal hydronephrosis. Management varies from simple monitoring to surgical intervention, with indications differing between institutions. A consensus of 8 societies recently described a new Urinary Tract Dilation (UTD) classification which aims to standardize ultrasound description of hydronephrosis, but which is also supposed to have predictive value in children with hydronephrosis. Our aim was to compare, in a monocentric prospective cohort of children with UPJO, the ability of UTD to predict the occurrence of a clinically significant event within the first year of life, as compared to anteroposterior diameter of the renal pelvis (APD).We used a preexisting cohort of children followed in a prospective study on UPJO. A pediatric radiologist, blinded to the children's' outcome, classified the last antenatal ultrasound and postnatal ultrasound according to the UTD-A and UTD-P classification. He also confirmed the APD-A and APD-P measures. We defined a clinically significant event as being: increased pelvic dilation (> 5 mm) and/or the presence of a febrile urinary tract infection (fUTI) and/or impaired renal function on initial nuclear scan (< 40%). We performed a ROC-AUC curve and Random Forest (RF) analysis to compare the ability of the APD-A, APD-P, UTD-A and UTD-P scores to predict a clinically significant event.The cohort included 28 children. Clinically significant events were noted in 20 out of 28 patients: 13 children presented an increase > 5 mm in dilation, 6 presented an episode of fUTI and 9 had impaired function of the affected kidney. APD-A was the most effective individual criterion for predicting the occurrence of a significant clinical event (AUC = 0.867).In our series, for children with UPJO, the most significant marker was prenatal APD >15mm to predict an increase in dilation > 5mm.